Pengaruh Public Service Motivation terhadap Organizational Citizenship Behavior: Peran Moderasi Service Climate - Mauludin, Dimas Prafi Al; Sari, Reza Lidia (Universitas Muria Kudus, 2024)
This study aims to analyse the effect of public service motivation (PSM) on organizational citizenship behaviour (OCB) and the moderating role of service climate in the relationship between the two variables in the context of the State Civil Apparatus in Indonesia. This research uses a cross-sectional study approach with a survey method and involves 105 state civil apparatus employees in East Java Province who serve for at least one year. The sample was drawn using accidental sampling technique. Participants completed an online questionnaire to measure the three research variables. PSM was measured with Public Service Motivation Scale (α:.81), service climate was measured with Service Climate Scale (α:.89), and OCB was measured OCB Scale (α:.94). The data analysis process in this study used moderated regression analysis techniques to test the research hypothesis. The results of this study indicate that public service motivation has a significant positive effect on organizational citizenship behavior, and service climate shows a significant positive moderating role in strengthening the relationship between public service motivation and organizational citizenship behavior.Penelitian ini bertujuan untuk menganalisis pengaruh public service motivation (PSM) terhadap organizational citizenship behavior (OCB) serta peran moderasi service climate dalam hubungan kedua variabel tersebut dalam konteks Aparatur Sipil Negara di Indonesia. Penelitian ini menggunakan pendekatan cross-sectional study dengan metode survei serta melibatkan 105 pegawai aparatur sipil negara di Provinsi Jawa Timur yang mengabdi sekurang-kurangnya selama satu tahun. Sampel diambil menggunakan teknik accidental sampling. Partisipan mengisi kuesioner daring untuk mengukur ketiga variabel penelitian. PSM diukur dengan menggunakan Public Service Motivation Scale (α:.81), service climate diukur dengan menggunakan Service Climate Scale (α:.89), dan OCB diukur dengan menggunakan OCB Scale (α:.94). Proses analisis data pada penelitian ini menggunakan teknik analisis moderated regression analysis untuk menguji hipotesis penelitian. Hasil pada penelitian ini menunjukkan bahwa public service motivation berpengaruh positif yang signifikan terhadap organizational citizenship behavior, serta service climate menunjukkan adanya peran moderasi positif yang signifikan dalam memperkuat hubungan antara public service motivation dengan organizational citizenship behavior.